APLIKASI METODA RES-2D UNTUK EKSPLORASI AIR BAWAH TANAH DI DAERAH KARS - Kuswanto, Agus (Center for Environmental Technology, 2005)
People have long been interested in kars, the typically topograhy in limestone area. There are many spectacular ornament in the caves caused by carbonates presipitates. Among the most common shapes which is be chief attraction for cave visitors is stalactites, stalagmites and columns.Ã‚Â Beside of the excitements, kars also have hard problem for people who lived in that area. It is how to find out water for their living.Ã‚Â Ã‚Â Karst formation, both the surface (dolina, hill, etc) and underground forms (caverns, groundwater conduits, underground streams), appears as conductive zones relative to adjacent undisturbed limestone.Ã‚Â Therefore resistivity methode will produce good results ifÃ‚Â applied to identify dolina, conduits , caverns and structure of geology in kars. The methodeÃ‚Â describes in this paper is Res-2D with configuration of pole-dipole with area for research are kars in Pacitan and Tulungagung region. Four principal layers can typically be differentiated in a vertical section : near surface (clayey) loam and soil in dolina, dry karstified limestone, conduit & cave and solid unkarstified limestone. They have contrast of resistivity. Conduits have resistivity value range from 10 to 20 ohmm, whereas resistivty of cave is > 1000 ohmm. Karstified limestone have resistivity value from 20 to 250 ohmm, whereas massive limestone have resistivity > 250 ohmm.Ã‚Â This paper shows that Res-2D methode can give good contribution in exploration of groundwater in kars area.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Kata Kunci : Kars, Res-2D, Conduits